Zhi-Zi-Chi Decoction Reverses Depressive Behaviors in CUMS Rats by Reducing Oxidative Stress Injury Via Regulating GSH/GSSG Pathway - Zhang, Yin; Fang, Yi-Chao; Cui, Li-Xun; Jiang, Yue-Tong; Luo, Yu-Sha; Zhang, Wen; Yu, De-Xun; Wen, Jun; Zhou, Ting-Ting (Frontiers in Pharmacology, 2022)
Depression is one of the main diseases that lead to disability and loss of ability to work. As a traditional Chinese medicine, Zhi-zi-chi decoction is utilized to regulate and improve depression. However, the research on the antidepressant mechanism and efficacy material basis of Zhi-zi-chi decoction has not been reported yet. Our previous research has found that Zhi-Zi-chi decoction can reduce glutamate-induced oxidative stress damage to PC 12 cells, which can exert a neuroprotective effect, and the antidepressant effect of Zhi-Zi-chi decoction was verified in CUMS rat models. In this study, the animal model of depression was established by chronic unpredictable mild stimulation combined with feeding alone. The brain metabolic profile of depressed rats was analyzed by the method of metabolomics based on ultra-performance liquid chromatography-quadrupole/time-of-flight mass. 26 differential metabolites and 6 metabolic pathways related to the antidepressant of Zhi-zi-chi decoction were screened and analyzed. The targeted metabolism of the glutathione metabolic pathway was analyzed. At the same time, the levels of reactive oxygen species, superoxide dismutase, glutathione reductase, glutathione peroxidase in the brain of depressed rats were measured. Combined with our previous study, the antioxidant effect of the glutathione pathway in the antidepressant effect of Zhi-zi-chi decoction was verified from the cellular and animal levels respectively. These results indicated that Zhi-zi-chi decoction exerted a potential antidepressive effect associated with reversing the imbalance of glutathione and oxidative stress in the brain of depressed rats.